Assessing supraglacial lake depth using ICESat-2, Sentinel-2, TanDEM-X, and in situ sonar measurements over Northeast and Southwest Greenland - Lutz, Katrina; Bever, Lily; Sommer, Christian; Seehaus, Thorsten; Humbert, Angelika; Scheinert, Mirko; Braun, Matthias (Cryosphere, 2024)
Supraglacial lake development in Greenland consists of intricate hydrological processes, contributing not only to surface mass loss but also to a lowering of the surface albedo and changes in ice dynamics. While the estimation of lake area has recently improved, the determination of the lake volume is essential to properly estimate the amount of water contained in and lost from supraglacial lakes throughout the melt seasons. In this study, four supraglacial lake depth estimation methods, including two new empirical approaches, are presented and compared. The empirical methods were developed to relate Sentinel-2 reflectance values to supraglacial lake depth obtained from (1) ICESat-2 (Ice, Cloud and land Elevation Satellite 2) crossings over 19 lakes in Northeast and Southwest Greenland and (2) in situ sonar tracks from four lakes on Zachariae Isstrom (Zachariæ Isstrøm) in Northeast Greenland. The depths from both equations were independently correlated to their corresponding Sentinel-2 reflectance values to create empirical relations. The third method is a standardly used radiative transfer model also based on Sentinel-2 data. Finally, the depths for five lakes in Northeast Greenland were derived from TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) digital elevation models after lake drainage. All four methods were applied to the five lakes for which digital elevation models were procured, allowing for a direct comparison of the methods. In general, the sonar-based empirical equation aligned best with the estimates from the digital elevation model until its saturation point of 8.6 m. Through the evaluation of the ICESat-2-based equation, a strong influence of lake bed sediment on depth estimation could be seen. The ICESat-2 empirically derived depth equation produced slightly deeper depths than the sonar-based equation. The radiative transfer model more strongly overestimated nearly all depths below its saturation point of 16.3 m, when compared to the digital elevation model results. This large overestimation can be primarily attributed to the sensitivity of this method’s parameters. Furthermore, all methods, with the exception of the digital elevation model, were applied to an area in Northeast Greenland on the peak melt dates for the years 2016–2022 to explore lake volume interannual variability. Finally, a closer examination of the uncertainties for each method provides insight into associated errors and limitations when considering which method to use for supraglacial lake depth estimation. Overall, empirically derived equations are shown to be capable of simplifying supraglacial lake depth calculations while also retaining sufficient accuracy under low-sediment, floating-ice-free, and atmospherically clear conditions.
CRIS-Team Scopus Importer:2024-12-13

Brief communication: Increased glacier mass loss in the Russian High Arctic (2010-2017) - Sommer, Christian; Seehaus, Thorsten; Glazovsky, Andrey; Braun, Matthias (Cryosphere, 2022)
Glaciers in the Russian High Arctic have been subject to extensive atmospheric warming due to global climate change, yet their contribution to sea level rise has been relatively small over the past decades. Here we show surface elevation change measurements and geodetic mass balances of 93% of all glacierized areas of Novaya Zemlya, Severnaya Zemlya, and Franz Josef Land using interferometric synthetic aperture radar measurements taken between 2010 and 2017. We calculate an overall mass loss rate of -22 +/- 6 Gt a(-1), corresponding to a sea level rise contribution of 0:06 +/- 0:02 mm a(-1). Compared to measurements prior to 2010, mass loss of glaciers on the Russian archipelagos has doubled in recent years.
CRIS-Team WoS Importer:2022-01-14

Changes of the tropical glaciers throughout Peru between 2000 and 2016 - Mass balance and area fluctuations - Seehaus, Thorsten; Malz, Philipp; Sommer, Christian; Lippl, Stefan; Cochachin, Alejo; Braun, Matthias (Cryosphere, 2019)
Glaciers in tropical regions are very sensitive to climatic variations and thus strongly affected by climate change. The majority of the tropical glaciers worldwide are located in the Peruvian Andes, which have shown significant ice loss in the last century. Here, we present the first multi-temporal, region-wide survey of geodetic mass balances and glacier area fluctuations throughout Peru covering the period 2000-2016. Glacier extents are derived from Landsat imagery by performing automatic glacier delineation based on a combination of the NDSI and band ratio method and final manual inspection and correction. The mapping of debris-covered glacier extents is supported by synthetic aperture radar (SAR) coherence information. A total glacier area loss of <span classCombining double low line"inline-formula"><math xmlnsCombining double low line"http://www.w3.org/1998/Math/MathML" idCombining double low line"M1" displayCombining double low line"inline" overflowCombining double low line"scroll" dspmathCombining double low line"mathml">-<mn mathvariantCombining double low line"normal">548.5±<mn mathvariantCombining double low line"normal">65.7<svg:svg xmlns:svgCombining double low line"http://www.w3.org/2000/svg" widthCombining double low line"70pt" heightCombining double low line"10pt" classCombining double low line"svg-formula" dspmathCombining double low line"mathimg" md5hashCombining double low line"4a56d867710ad1d0e6b59b40efc7543a"><svg:image xmlns:xlinkCombining double low line"http://www.w3.org/1999/xlink" xlink:hrefCombining double low line"tc-13-2537-2019-ie00001.svg" widthCombining double low line"70pt" heightCombining double low line"10pt" srcCombining double low line"tc-13-2537-2019-ie00001.png"/></svg:svg> km<span classCombining double low line"inline-formula">2 (<span classCombining double low line"inline-formula">-29 %, <span classCombining double low line"inline-formula">-34.3 km<span classCombining double low line"inline-formula">2 a<span classCombining double low line"inline-formula">-1) is obtained for the study period. Using interferometric satellite SAR acquisitions, bi-temporal geodetic mass balances are derived. An average specific mass balance of <span classCombining double low line"inline-formula"><math xmlnsCombining double low line"http://www.w3.org/1998/Math/MathML" idCombining double low line"M7" displayCombining double low line"inline" overflowCombining double low line"scroll" dspmathCombining double low line"mathml">-<mn mathvariantCombining double low line"normal">296±<mn mathvariantCombining double low line"normal">41<svg:svg xmlns:svgCombining double low line"http://www.w3.org/2000/svg" widthCombining double low line"52pt" heightCombining double low line"10pt" classCombining double low line"svg-formula" dspmathCombining double low line"mathimg" md5hashCombining double low line"daccc0027f423fe62c08bfd3497e240a"><svg:image xmlns:xlinkCombining double low line"http://www.w3.org/1999/xlink" xlink:hrefCombining double low line"tc-13-2537-2019-ie00002.svg" widthCombining double low line"52pt" heightCombining double low line"10pt" srcCombining double low line"tc-13-2537-2019-ie00002.png"/></svg:svg> kg m<span classCombining double low line"inline-formula">-2 a<span classCombining double low line"inline-formula">-1 is found throughout Peru for the period 2000-2016. However, there are strong regional and temporal differences in the mass budgets ranging from <span classCombining double low line"inline-formula">45±97 to <span classCombining double low line"inline-formula"><math xmlnsCombining double low line"http://www.w3.org/1998/Math/MathML" idCombining double low line"M11" displayCombining double low line"inline" overflowCombining double low line"scroll" dspmathCombining double low line"mathml">-<mn mathvariantCombining double low line"normal">752±<mn mathvariantCombining double low line"normal">452<svg:svg xmlns:svgCombining double low line"http://www.w3.org/2000/svg" widthCombining double low line"58pt" heightCombining double low line"10pt" classCombining double low line"svg-formula" dspmathCombining double low line"mathimg" md5hashCombining double low line"fcf2e06ca9213df129dd310b27a4dc03"><svg:image xmlns:xlinkCombining double low line"http://www.w3.org/1999/xlink" xlink:hrefCombining double low line"tc-13-2537-2019-ie00003.svg" widthCombining double low line"58pt" heightCombining double low line"10pt" srcCombining double low line"tc-13-2537-2019-ie00003.png"/></svg:svg> kg m<span classCombining double low line"inline-formula">-2 a<span classCombining double low line"inline-formula">-1. The ice loss increased towards the end of the observation period. Between 2013 and 2016, a retreat of the glacierized area of <span classCombining double low line"inline-formula"><math xmlnsCombining double low line"http://www.w3.org/1998/Math/MathML" idCombining double low line"M14" displayCombining double low line"inline" overflowCombining double low line"scroll" dspmathCombining double low line"mathml">-<mn mathvariantCombining double low line"normal">203.8±<mn mathvariantCombining double low line"normal">65.7<svg:svg xmlns:svgCombining double low line"http://www.w3.org/2000/svg" widthCombining double low line"70pt" heightCombining double low line"10pt" classCombining double low line"svg-formula" dspmathCombining double low line"mathimg" md5hashCombining double low line"ea393321be0a3323d1a14edbade0f209"><svg:image xmlns:xlinkCombining double low line"http://www.w3.org/1999/xlink" xlink:hrefCombining double low line"tc-13-2537-2019-ie00004.svg" widthCombining double low line"70pt" heightCombining double low line"10pt" srcCombining double low line"tc-13-2537-2019-ie00004.png"/></svg:svg> km<span classCombining double low line"inline-formula">2 (<span classCombining double low line"inline-formula">-16 %, <span classCombining double low line"inline-formula">-101.9 km<span classCombining double low line"inline-formula">2 a<span classCombining double low line"inline-formula">-1) is mapped and the average mass budget amounts to <span classCombining double low line"inline-formula"><math xmlnsCombining double low line"http://www.w3.org/1998/Math/MathML" idCombining double low line"M20" displayCombining double low line"inline" overflowCombining double low line"scroll" dspmathCombining double low line"mathml">-<mn mathvariantCombining double low line"normal">660±<mn mathvariantCombining double low line"normal">178<svg:svg xmlns:svgCombining double low line"http://www.w3.org/2000/svg" widthCombining double low line"58pt" heightCombining double low line"10pt" classCombining double low line"svg-formula" dspmathCombining double low line"mathimg" md5hashCombining double low line"4d564a6ec6bec32c37de7ae43c3acb5d"><svg:image xmlns:xlinkCombining double low line"http://www.w3.org/1999/xlink" xlink:hrefCombining double low line"tc-13-2537-2019-ie00005.svg" widthCombining double low line"58pt" heightCombining double low line"10pt" srcCombining double low line"tc-13-2537-2019-ie00005.png"/></svg:svg> kg m<span classCombining double low line"inline-formula">-2 a<span classCombining double low line"inline-formula">-1. The glacier changes revealed can be attributed to changes in the climatic settings in the study region, derived from ERA-Interim reanalysis data and the Oceanic Nino Index. The intense El Niño activities in 2015/16 are most likely the trigger for the increased change rates in the time interval 2013-2016. Our observations provide fundamental information on the current dramatic glacier changes for local authorities and for the calibration and validation of glacier change projections.
CRIS-Team Scopus Importer:2019-10-08

Climate’s firm grip on glacier ablation in the Cordillera Darwin Icefield, Tierra del Fuego - Temme, Franziska; Sommer, Christian; Schaefer, Marius; Jaña, Ricardo; Arigony-Neto, Jorge; Gonzalez, Inti; Izagirre, Eñaut; Giesecke, Ricardo; Tetzner, Dieter; Fürst, Johannes (Nature Communications, 2025)
The Cordillera Darwin Icefield (CDI) in Tierra del Fuego is one of the largest temperate ice bodies in the Southern Hemisphere. We simulate the climatic energy and mass balance of its glaciers (2000–2023), which are sensitive indicators of climatic changes in the Southern Hemisphere’s higher mid-latitudes. Year-round westerly winds cause strong climatic gradients across the mountain range, reflected in the energy and mass fluxes. Our results reveal a significant increase in surface melt (+0.18 m w.e. yr-1 per decade) over the past two decades. We also present the first estimate of dynamically controlled mass loss into adjacent fjords and lakes by frontal ablation, amounting to 1.44 ± 0.94 Gt yr-1 (26 % of the total CDI mass loss). Frontal losses are mainly channelized through few marine-terminating glaciers. While frontal ablation is important for predicting the fate of individual glaciers, for the CDI as a whole, atmospheric conditions exert the main control on the current glacier evolution.
CRIS-Team Scopus Importer:2025-04-01

Constraining glacier elevation and mass changes in South America - Braun, Matthias; Malz, Philipp; Sommer, Christian; Farías Barahona, David; Sauter, Tobias; Casassa, Gino; Soruco, Alvaro; Skvarca, Pedro; Seehaus, Thorsten (Nature Climate Change, 2019)
Excluding the large ice sheets of Greenland and Antarctica, glaciers in South America are large contributors to sea-level rise<a title="Marzeion, B., Kaser, G., Maussion, F. & Champollion, N. Limited influence of climate change mitigation on short-term glacier mass loss. Nat. Clim. Change 8, 305–308 (2018)." href="https://www.nature.com/articles/s41558-018-0375-7#ref-CR1">1. Their rates of mass loss, however, are poorly known. Here, using repeat bi-static synthetic aperture radar interferometry over the years 2000 to 2011/2015, we compute continent-wide, glacier-specific elevation and mass changes for 85% of the glacierized area of South America. Mass loss rate is calculated to be 19.43 ± 0.60 Gt a−1 from elevation changes above ground, sea or lake level, with an additional 3.06 ± 1.24 Gt a−1 from subaqueous ice mass loss not contributing to sea-level rise. The largest contributions come from the Patagonian icefields, where 83% mass loss occurs, largely from dynamic adjustments of large glaciers. These changes contribute 0.054 ± 0.002 mm a−1 to sea-level rise. In comparison with previous studies2, tropical and out-tropical glaciers — as well as those in Tierra del Fuego — show considerably less ice loss. These results provide basic information to calibrate and validate glacier-climate models and also for decision-makers in water resource management3</sup
Keywords: SAR; Interferometry; glacier elevation change; glacier mass balance; TanDEM-X; SRTM; Andes; South America; Patagonia; geodetic

Constraining regional glacier reconstructions using past ice thickness of deglaciating areas - a case study in the European Alps - Sommer, Christian; Fürst, Johannes; Huss, Matthias; Braun, Matthias (Cryosphere, 2023)
In order to assess future glacier evolution and meltwater runoff, accurate knowledge on the volume and the ice thickness distribution of glaciers is crucial. However, in situ observations of glacier thickness are sparse in many regions worldwide due to the difficulty of undertaking field surveys. This lack of in situ measurements can be partially overcome by remote-sensing information. Multi-temporal and contemporaneous data on glacier extent and surface elevation provide past information on ice thickness for retreating glaciers in the newly deglacierized regions. However, these observations are concentrated near the glacier snouts, which is disadvantageous because it is known to introduce biases in ice thickness reconstruction approaches. Here, we show a strategy to overcome this generic limitation of so-called retreat thickness observations by applying an empirical relationship between the ice viscosity at locations with in situ observations and observations from digital elevation model (DEM) differencing at the glacier margins. Various datasets from the European Alps are combined to model the ice thickness distribution of Alpine glaciers for two time steps (1970 and 2003) based on the observed thickness in regions uncovered from ice during the study period. Our results show that the average ice thickness would be substantially underestimated (∼40%) when relying solely on thickness observations from previously glacierized areas. Thus, a transferable topography-based viscosity scaling is developed to correct the modelled ice thickness distribution. It is shown that the presented approach is able to reproduce region-wide glacier volumes, although larger uncertainties remain at a local scale, and thus might represent a powerful tool for application in regions with sparse observations.
CRIS-Team Scopus Importer:2024-12-16

Continent wide monitoring of glacier surface elevation changes and glacer mass balances - Seehaus, Thorsten; Malz, Philipp; Sommer, Christian; Farías Barahona, David; Braun, Matthias (Proceedings of 2019 Big Data from Space, 2019)

Detailed quantification of glacier elevation and mass changes in South Georgia - Farías Barahona, David; Sommer, Christian; Sauter, Tobias; Bannister, Daniel; Seehaus, Thorsten; Malz, Philipp; Casassa, Gino; Mayewski, Paul A.; Turton, Jenny; Braun, Matthias (Environmental Research Letters, 2020)

Distributed Global Debris Thickness Estimates Reveal Debris Significantly Impacts Glacier Mass Balance - Rounce, D. R.; Hock, R.; McNabb, R. W.; Millan, R.; Sommer, Christian; Braun, Matthias; Malz, Philipp; Maussion, F.; Mouginot, J.; Seehaus, Thorsten; Shean, D. E. (Geophysical Research Letters, 2021)
Supraglacial debris affects glacier mass balance as a thin layer enhances surface melting, while a thick layer reduces it. While many glaciers are debris-covered, global glacier models do not account for debris because its thickness is unknown. We provide the first globally distributed debris thickness estimates using a novel approach combining sub-debris melt and surface temperature inversion methods. Results are evaluated against observations from 22 glaciers. We find the median global debris thickness is ∼0.15 ± 0.06 m. In all regions, the net effect of accounting for debris is a reduction in sub-debris melt, on average, by 37%, which can impact regional mass balance by up to 0.40 m water equivalent (w.e.) yr-1. We also find recent observations of similar thinning rates over debris-covered and clean ice glacier tongues is primarily due to differences in ice dynamics. Our results demonstrate the importance of accounting for debris in glacier modeling efforts.
CRIS-Team Scopus Importer:2021-05-14
Keywords: debris thickness; glacier melt; glaciers; mass balance

Geodetic Mass Balance of the South Shetland Islands Ice Caps, Antarctica, from Differencing TanDEM-X DEMs - Shahateet, Kaian; Seehaus, Thorsten; Navarro, Francisco; Sommer, Christian; Braun, Matthias (Remote Sensing, 2021)
Although the glaciers in the Antarctic periphery currently modestly contribute to sea level rise, their contribution is projected to increase substantially until the end of the 21st century. The South Shetland Islands (SSI), located to the north of the Antarctic Peninsula, are lacking a geodetic mass balance calculation for the entire archipelago. We estimated its geodetic mass balance over a 3–4-year period within 2013–2017. Our estimation is based on remotely sensed multispectral and interferometric SAR data covering 96% of the glacierized areas of the islands considered in our study and 73% of the total glacierized area of the SSI archipelago (Elephant, Clarence, and Smith Islands were excluded due to data limitations). Our results show a close to balance, slightly negative average specific mass balance for the whole area of −0.106 ± 0.007 m w.e. a−1, representing a mass change of −238 ± 12 Mt a−1. These results are consistent with a wider scale geodetic mass balance estimation and with glaciological mass balance measurements at SSI locations for the same study period. They are also consistent with the cooling trend observed in the region between 1998 and the mid-2010s
Keywords: SAR; remote sensing; glacier; Antarctic Peninsula; Antarctic periphery; ice loss

Global glacier surface elevation change and geodetic mass balance estimations - Malz, Philipp; Sommer, Christian; Seehaus, Thorsten; Farías-Barahona, David; Braun, Matthias (Proceedings of the European Conference on Synthetic Aperture Radar, EUSAR, 2021)
Glaciers worldwide undergo drastic adaption caused by climate change. A detailed knowledge about their status is of broad public interest, as glaciers are freshwater resources and drivers of sea level change. We aim at providing elevation change rates for mountain glaciers worldwide between 60° N and 56° S and respective geodetic mass balance. Therefore, we derive DEMs from TanDEM-X CoSSC datasets via own dInSAR processing. These DEMs are referenced, aligned and compared to SRTM V.3 DEMs. Resulting elevation change information are converted to mass balance and result to -64.5±2.8 Gt a-1 on 184,056 km2 (SRTM constraints).
CRIS-Team Scopus Importer:2021-06-04

Mass and enthalpy budget evolution during the surge of a polythermal glacier: A test of theory - Benn, Douglas I.; Jones, Robert L.; Luckman, Adrian; Fürst, Johannes; Hewitt, Ian; Sommer, Christian (Journal of Glaciology, 2019)
Analysis of a recent surge of Morsnevbreen, Svalbard, is used to test predictions of the enthalpy balance theory of surging. High-resolution time series of velocities, ice thickness and crevasse distribution allow key elements of the enthalpy (internal energy) budget to be quantified for different stages of the surge cycle. During quiescence (1936-1990), velocities were very low, and geothermal heat slowly built-up enthalpy at the bed. Measurable mass transfer and frictional heating began in 1990-2010, then positive frictional heating-velocity feedbacks caused gradual acceleration from 2010 to 2015. Rapid acceleration occurred in summer 2016, when extensive crevassing and positive air temperatures allowed significant surface to bed drainage. The surge front reached the terminus in October 2016, coincident with a drop in velocities. Ice plumes in the fjord are interpreted as discharge of large volumes of supercooled water from the bed. Surge termination was prolonged, however, indicating persistence of an inefficient drainage system. The observations closely match predictions of the theory, particularly build-up of enthalpy from geothermal and frictional heat, and surface meltwater, and the concomitant changes in ice-surface elevation and velocity. Additional characteristics of the surge reflect spatial processes not represented in the model, but can be explained with respect to enthalpy gradients.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Arctic glaciology; glacier surges; ice dynamics

Mass balance and area changes of glaciers in the Cordillera Real and Tres Cruces, Bolivia, between 2000 and 2016 - Seehaus, Thorsten; Malz, Philipp; Sommer, Christian; Soruco, Alvaro; Rabatel, Antoine; Braun, Matthias (Journal of Glaciology, 2020)

Mass changes of the northern Antarctic Peninsula Ice Sheet derived from repeat bi-static synthetic aperture radar acquisitions for the period 2013–2017 - Seehaus, Thorsten; Sommer, Christian; Dethinne, Thomas; Malz, Philipp (Cryosphere, 2023)
Some of the highest specific mass change rates in Antarctica are reported for the Antarctic Peninsula. However, the existing estimates for the northern Antarctic Peninsula (<70∘ S) are either spatially limited or are affected by considerable uncertainties. The complex topography, frequent cloud cover, limitations in ice thickness information, boundary effects, and uncertain glacial–isostatic adjustment estimates affect the ice sheet mass change estimates using altimetry, gravimetry, or the input-output method. Within this study, the first assessment of the geodetic mass balance throughout the ice sheet of the northern Antarctic Peninsula is carried out employing bi-static synthetic aperture radar (SAR) data from the TanDEM-X satellite mission. Repeat coverages from the austral winters of 2013 and 2017 are employed. Overall, coverage of 96.4 % of the study area by surface elevation change measurements and a total mass budget of Gt a−1 are revealed. The spatial distribution of the surface elevation and mass changes points out that the former ice shelf tributary glaciers of the Prince Gustav Channel, Larsen A and B, and Wordie ice shelves are the hotspots of ice loss in the study area and highlights the long-lasting dynamic glacier adjustments after the ice shelf break-up events. The highest mass change rate is revealed for the Airy–Seller–Fleming glacier system at Gt a−1, and the highest average surface elevation change rate of m a−1 is observed at Drygalski Glacier. The comparison of the ice mass budget with anomalies in the climatic mass balance indicates, that for wide parts of the southern section of the study area, the mass changes can be partly attributed to changes in the climatic mass balance. However, imbalanced high ice discharge drives the overall ice loss. The previously reported connection between mid-ocean warming along the southern section of the west coast and increased frontal glacier recession does not repeat in the pattern of the observed glacier mass losses, excluding in Wordie Bay. The obtained results provide information on ice surface elevation and mass changes for the entire northern Antarctic Peninsula on unprecedented spatially detailed scales and with high precision and will be beneficial for subsequent analysis and modeling.<br

Observing glacier elevation changes from spaceborne optical and radar sensors - an inter-comparison experiment using ASTER and TanDEM-X data - Piermattei, Livia; Zemp, Michael; Sommer, Christian; Brun, Fanny; Braun, Matthias; Andreassen, Liss M.; Belart, Joaquín M.C.; Berthier, Etienne; Bhattacharya, Atanu; Boehm Vock, Laura; Bolch, Tobias; Dehecq, Amaury; et al. (Cryosphere, 2024)
Observations of glacier mass changes are key to understanding the response of glaciers to climate change and related impacts, such as regional runoff, ecosystem changes, and global sea level rise. Spaceborne optical and radar sensors make it possible to quantify glacier elevation changes, and thus multi-annual mass changes, on a regional and global scale. However, estimates from a growing number of studies show a wide range of results with differences often beyond uncertainty bounds. Here, we present the outcome of a community-based inter-comparison experiment using spaceborne optical stereo (ASTER) and synthetic aperture radar interferometry (TanDEM-X) data to estimate elevation changes for defined glaciers and target periods that pose different assessment challenges. Using provided or self-processed digital elevation models (DEMs) for five test sites, 12 research groups provided a total of 97 spaceborne elevation-change datasets using various processing approaches. Validation with airborne data showed that using an ensemble estimate is promising to reduce random errors from different instruments and processing methods but still requires a more comprehensive investigation and correction of systematic errors. We found that scene selection, DEM processing, and co-registration have the biggest impact on the results. Other processing steps, such as treating spatial data voids, differences in survey periods, or radar penetration, can still be important for individual cases. Future research should focus on testing different implementations of individual processing steps (e.g. co-registration) and addressing issues related to temporal corrections, radar penetration, glacier area changes, and density conversion. Finally, there is a clear need for our community to develop best practices, use open, reproducible software, and assess overall uncertainty to enhance inter-comparison and empower physical process insights across glacier elevation-change studies.
CRIS-Team Scopus Importer:2024-07-26

Rapid glacier retreat and downwasting throughout the European Alps in the early 21st century - Sommer, Christian; Malz, Philipp; Seehaus, Thorsten; Lippl, Stefan; Zemp, Michael; Braun, Matthias (Nature Communications, 2020)
Mountain glaciers are known to be strongly affected by global climate change. Here we compute temporally consistent changes in glacier area, surface elevation and ice mass over the entire European Alps between 2000 and 2014. We apply remote sensing techniques on an extensive database of optical and radar imagery covering 93% of the total Alpine glacier volume. Our results reveal rapid glacier retreat across the Alps (−39 km² a−1) with regionally variable ice thickness changes (−0.5 to −0.9 m a−1). The strongest downwasting is observed in the Swiss Glarus and Lepontine Alps with specific mass change rates up to −1.03 m.w.e. a−1. For the entire Alps a mass loss of 1.3 ± 0.2 Gt a−1 (2000–2014) is estimated. Compared to previous studies, our estimated mass changes are similar for the central Alps, but less negative for the lower mountain ranges. These observations provide important information for future research on various socio-economic impacts like water resource management, risk assessments and tourism.
CRIS-Team Scopus Importer:2020-07-03